Fractioning HiPco and CoMoCAT SWCNTs via density gradient ultracentrifugation by the aid of a novel perylene bisimide derivative surfactant - Backes, Claudia; Hauke, Frank; Schmidt, Cordula; Hirsch, Andreas (Chemical Communications, 2009)
HiPco and CoMoCAT single-walled carbon nanotubes (SWCNT) were fractionated with the aid of a novel perylene bisimide surfactant by combined co-surfactant and replacement density gradient ultracentrifugation (DGU). © The Royal Society of Chemistry 2009.